Legal Efforts of Justice Collaborator In Corruption Crime - Ferry Vincentius (Faculty of Law, Merdeka University Surabaya, 2021)
In writing this paper the author discusses about Legal Effort for Cooperating Witness (Justice Collaborators) in Corruption Crime. This is motivated by legal effort because of the lack of legal protection for the actors who Cooperating Witness (Justice Collaborators) in Indonesia. So the author wants to do a juridical study of the status of the Cooperating Witness (Justice Collaborators) and the legal effort of the witnesses who are status as Cooperating Witness (Justice Collaborators).This is done to find a concept that can be incorporated into the criminal justice system in Indonesia. So that it is hoped that a good form of protection will be created for the Cooperating Witness (Justice Collaborators) who in the end can be a good step to provide opportunities for the public to provide information and information in uncovering serious and organized crimes in the future.